Geodynamic controls on the contamination of Cenozoic arc magmas in the southern Central Andes: Insights from the O and Hf isotopic composition of zircon. (1st September 2015) - Jones, Rosemary E.; Kirstein, Linda A.; Kasemann, Simone A.; Dhuime, Bruno; Elliott, Tim; Litvak, Vanesa D.; Alonso, Ricardo; Hinton, Richard; ,
Abstract: Subduction zones, such as the Andean convergent margin of South America, are sites of active continental growth and crustal recycling. The composition of arc magmas, and therefore new continental crust, reflects variable contributions from mantle, crustal and subducted reservoirs. Temporal (Ma) and spatial (km) variations in these contributions to southern Central Andean arc magmas are investigated in relation to the changing plate geometry and geodynamic setting of the southern Central Andes (28–32° S) during the Cenozoic. The in-situ analysis of O and Hf isotopes in zircon, from both intrusive (granitoids) and extrusive (basaltic andesites to rhyolites) Late Cretaceous – Late Miocene arc magmatic rocks, combined with high resolution U–Pb dating, demonstrates distinct across-arc variations. Mantle-like δ 18 O(zircon) values (+5.4‰ to +5.7‰ (±0.4 (2 σ ))) and juvenile initial εHf(zircon) values (+8.3 (±0.8 (2 σ )) to +10.0 (±0.9 (2 σ ))), combined with a lack of zircon inheritance suggests that the Late Cretaceous (∼73 Ma) to Eocene (∼39 Ma) granitoids emplaced in the Principal Cordillera of Chile formed from mantle-derived melts with very limited interaction with continental crustal material, therefore representing a sustained period of upper crustal growth. Late Eocene (∼36 Ma) to Early Miocene (∼17 Ma) volcanic arc rocks present in the Frontal Cordillera have 'mantle-like' δ 18 O(zircon) values (+4.8‰ (±0.2 (2 σ ) to +5.8‰ (±0.5 (2 σ ))), but less radiogenic initial εHf(zircon) values (+1.0 (±1.1 (2 σ )) to +4.0 (±0.6 (2 σ ))) providing evidence for mixing of mantle-derived melts with the Late Paleozoic – Early Mesozoic basement (up to ∼20%). The assimilation of both Late Paleozoic – Early Mesozoic Andean crust and a Grenville-aged basement is required to produce the higher than 'mantle-like' δ 18 O(zircon) values (+5.5‰ (±0.6 (2 σ ) to +7.2‰ (±0.4 (2 σ ))) and unradiogenic, initial εHf(zircon) values (−3.9 (±1.0 (2 σ )) to +1.6 (±4.4 (2 σ ))), obtained for the Late Oligocene (∼23 Ma) to Late Miocene (∼9 Ma) magmatic rocks located in the Argentinean Precordillera, and the Late Miocene (∼6 Ma) volcanic rocks present in the Frontal Cordillera. The observed isotopic variability demonstrates that the assimilation of pre-existing continental crust, which varies in both age and composition over the Andean Cordillera, plays a dominant role in modifying the isotopic composition of Late Eocene to Late Miocene mantle-derived magmas, implying significant crustal recycling. The interaction of arc magmas with distinct basement terranes is controlled by the migration of the magmatic arc due to the changing geodynamic setting, as well as by the tectonic shortening and thickening of the Central Andean crust over the latter part of the Cenozoic.